Juan de Mariana et l’apostolat de plume - Claire Bouvier (E-Spania)
This article would like to study Juan de Mariana as a Jesuit scriptor. The examination of the catalogs of the personnel of the Society of Jesus, which have no equivalent in the other religious orders, gives an account of the progressive institutionalization of a new apostolate, the one of pen, and the appearance of the figure of the scriptor, of which Juan de Mariana was one of the first representatives. Reconstructing the literary career of Juan de Mariana from a purely institutional point of view allows us to examine the formation of a corporation of specialists of what is written in the Ignatian order, as well as the growing autonomy of the literary apostolate.